Forest Soil Organic Carbon Stocks of Tessala Mount in North-West Algeria-Preliminary Estimates - Merabtene, Mohammed Djemel; Faraoun, Fatiha; Mlih, Rawan; Djellouli, Riad; Latreche, Ali; Bol, Roland (Frontiers in Environmental Science, 2021)
Mountainous forests in Algeria are severely affected by climate change. The degradation is exacerbated by overgrazing, deforestation, and poor land management linked to the harsh topographical conditions of the mountain agrosystem. These conditions have influenced the turnover of the SOM and thus the SOC stocks storage. The aim of this study is to investigate the average of organic carbon stored in forest soils of Tessala mount in Algeria, and to examine the influence of different plant formations alongside with geographical characteristics and soil physicochemical properties on the amount of carbon stored in the soil. We estimated the critical threshold, the saturation point and the organic carbon deficit of soils. The Correlation between geographical characteristics and soil physicochemical properties and soil organic carbon stocks was determined using principle component analysis and other statistical tools. The results of the study show that the organic carbon stock in mount soils of Tessala area has an average value of 77.4 t ha-1. The organic carbon sequestration of the topsoil in Tessala region was positively correlated with coarse silt, elevation, and northern exposure, but negatively with calcium carbonates contents. The current carbon contents of Tessala topsoil is 22 g C kg-1 which is very low and closer to the critical threshold (11 g C kg-1). The estimated maximum storage capacity is 160 g C kg-1.